Does the Pederson Difficulty Index Accurately Predict the Difficulty of Mandibular Third Molar Extraction? - Njokanma, Azuka; Aborisade, Adetayo; Kuye, Olasunkanmi; Amedari, Mcking; Njokanma, Ada (Nigerian Journal of Basic and Clinical Sciences, 2025)
Context This study aimed to determine the relationship between the Pederson Difficulty Index and the Modified Parant Scale, and to evaluate the effectiveness of the Pederson Index in predicting the difficulty of mandibular third molar extractions. Settings and Design A cross-sectional study was conducted among patients indicated for mandibular third molar extraction. The Pederson Difficulty Index was used preoperatively to assess anticipated extraction difficulty, while postoperative assessment was carried out using the Modified Parant Scale. Methods Eighty-five participants scheduled for surgical extraction of mandibular third molars under local anaesthesia were recruited between February and July 2018. The relationships between the Pederson Difficulty Index, Modified Parant Scale scores, and duration of extraction were examined. Descriptive statistics summarized sociodemographic data. Student’s t-test was used to compare group means, and correlations were computed between the Pederson Index, Modified Parant Scale, and surgery duration. Results The study included 85 participants with a mean age of 25.8 ± 4.6 years, with no significant gender difference (p = 0.87). The Pederson Difficulty Index showed a sensitivity of 46.4% and a specificity of 89.5%. A moderate correlation was observed between the Pederson Index and duration of surgery (r = 0.35, p < 0.001), as well as between the Pederson Index and Modified Parant Scale scores (r = 0.36, p < 0.001). Conclusion Preoperative assessment is essential for predicting the difficulty of mandibular third molar extraction. While the Pederson Difficulty Index demonstrates moderate predictive value, its relatively low sensitivity raises concerns regarding its reliability as a sole predictor of surgical difficulty.